2019
DOI: 10.1002/adom.201801337
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Bifunctional Dielectric Metasurface Enabling Polarization‐Tuned Focusing and Deflection for Visible Light

Abstract: A multifunctional metasurface has attracted drastically growing interest, serving as a prominent candidate to cope with both device miniaturization and integration. Conventional transmissive bifunctional metasurfaces working for visible light inherently suffer from several demerits owing to the use of geometric phase and spatial multiplexing scheme. Research endeavors have been mainly devoted to the implementation of a static device. In this work, a highly efficient bifunctional dielectric metasurface, taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Gao et al proposed and demonstrated a highly efficient bifunctional dielectric metasurface, whose building block capitalizes on anisotropic nanoposts made up of hydrogenated amorphous Si, as shown in Figure a. [ 82 ] Therefore, visible polarization‐encoded focusing and anomalous beam‐steering were implemented. By tailoring the unit cell's periodicity, the angle of beam deflection and distance of focusing can be effectively tuned.…”
Section: Polarization‐multiplexed Metadevicesmentioning
confidence: 99%
“…Gao et al proposed and demonstrated a highly efficient bifunctional dielectric metasurface, whose building block capitalizes on anisotropic nanoposts made up of hydrogenated amorphous Si, as shown in Figure a. [ 82 ] Therefore, visible polarization‐encoded focusing and anomalous beam‐steering were implemented. By tailoring the unit cell's periodicity, the angle of beam deflection and distance of focusing can be effectively tuned.…”
Section: Polarization‐multiplexed Metadevicesmentioning
confidence: 99%
“…The relative local phase and phase gradient can be calculated using the measured positions of focuses in a sub-pixel. The polarization multifunctionality of the metalens can also provide various opportunities for multiplexing deflection and focusing (Gao et al, 2019a) and for multi-generation of an optical vortex (Wang et al, 2020b). In addition to multifunctionality of polarization and frequency, angle multifunctional metalens gives miniaturized and powerful tools to quantitative phase imaging.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Being flat and ultrathin, metasurfaces can effectively reduce the size and weight of many optical systems, attracting increasing research interest in recent years. Researchers have demonstrated a plethora of ultrathin and flat optical devices based on metasurfaces, including metalens [8,9], beam deflectors [10,11], meta-holograms [12,13], color filters [14,15], optical vortex generators [16,17], nonlinear [18,19] and even quantum [20,21] optical devices, etc. Among them, Li et al demonstrated for the first time a Cassegrain telescope based on two flat, ultrathin metasurfaces operating in the infrared wavelength range [22], opening up a new avenue to circumvent difficulties faced by reflective optics with curved surfaces.…”
Section: Introductionmentioning
confidence: 99%